Interfacial Adhesion of Thick NiTi Coating on Substrate Stainless Steel - Samal, Sneha; Kopeček, Jaromír; Šittner, Petr (Materials (Basel, Switzerland), 2022)
Interfacial adhesion of thick NiTi coating on substrate stainless steel is investigated here. NiTi coating was deposited on the substrate by using the thermal plasma spraying method. Deposition of NiTi coating was carried out by using various levels of input power under an Ar atmosphere. Multiple coating layers were deposited on the stainless steel surface for a specific thickness. The cross-section of the plasma-sprayed samples were prepared and characterized by using various techniques. The hardness of the coating layers on the surface and cross-section was examined. The thickness of the coating increased with the increase in power. No cracks were detected in the interface for the NiTi coating deposited at 12 kW power. However minor pores were observed at some regions along the interface at the sample prepared at 9 kW power. A good-quality coating layer was formed at the interface of the substrate. Primary phases of austenite and martensite were confirmed from the EBSD and XRD investigations. There was the presence of intermetallic and oxide phases in the coating layers. A less heat-affected zone of 10 µm of along the interface was confirmed without any diffusion of elements from the substrate to the coating layers. There was homogenous distribution elemental composition of Ni and Ti throughout the coating layers.
Keywords: stainless steel substrate; NiTi; plasma process; thick layer